An advanced optical clearing protocol allows label-free detection of tissue necrosis via multiphoton microscopy in injured whole muscle - Schneidereit, Dominik; Broellochs, Anita; Ritter, Paul; Kreiß, Lucas; Mokhtari, Zeinab; Beilhack, Andreas; Krönke, Gerhard; Ackermann, Jochen; Faas, Maria; Grüneboom, Anika; Schürmann, Sebastian; Friedrich, Oliver (Theranostics, 2021)
Rationale: Structural remodeling or damage as a result of disease or injury is often not evenly distributed throughout a tissue but strongly depends on localization and extent of damaging stimuli. Skeletal muscle as a mechanically active organ can express signs of local or even systemic myopathic damage, necrosis, or repair. Conventionally, muscle biopsies (patients) or whole muscles (animal models) are mechanically sliced and stained to assess structural alterations histologically. Three-dimensional tissue information can be obtained by applying deep imaging modalities, e.g. multiphoton or light-sheet microscopy. Chemical clearing approaches reduce scattering, e.g. through matching refractive tissue indices, to overcome optical penetration depth limits in thick tissues.
CRIS-Team WoS Importer:2021-01-22

IL-33-induced metabolic reprogramming controls the differentiation of alternatively activated macrophages and the resolution of inflammation - Faas, Maria; Ipseiz, Natacha; Ackermann, Jochen; Culemann, Stephan; Grüneboom, Anika; Schröder, Fenja; Rothe, Tobias; Scholtysek, Carina; Eberhardt, Martin; Böttcher, Martin; Kirchner, Philipp; Stoll, Cornelia; et al. (Immunity, 2021)
Alternatively activated macrophages (AAMs) contribute to the resolution of inflammation and tissue repair. However, molecular pathways that govern their differentiation have remained incompletely understood. Here, we show that uncoupling protein-2-mediated mitochondrial reprogramming and the transcription factor GATA3 specifically controlled the differentiation of pro-resolving AAMs in response to the alarmin IL-33. In macrophages, IL-33 sequentially triggered early expression of pro-inflammatory genes and subsequent differentiation into AAMs. Global analysis of underlying signaling events revealed that IL-33 induced a rapid metabolic rewiring of macrophages that involved uncoupling of the respiratory chain and increased production of the metabolite itaconate, which subsequently triggered a GATA3-mediated AAM polarization. Conditional deletion of GATA3 in mononuclear phagocytes accordingly abrogated IL-33-induced differentiation of AAMs and tissue repair upon muscle injury. Our data thus identify an IL-4-independent and GATA3-dependent pathway in mononuclear phagocytes that results from mitochondrial rewiring and controls macrophage plasticity and the resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: alternatively activated macrophage; GATA3; interleukin-33; itaconate; mitochondrial rewiring; resolution of inlammation; UCP2; uncoupling

Locally renewing resident synovial macrophages provide a protective barrier for the joint - Culemann, Stephan; Grüneboom, Anika; Nicolás-Ávila, José Ángel; Weidner, Daniela; Lämmle, Katrin Franziska; Rothe, Tobias; Quintana, Juan A.; Kirchner, Philipp; Krljanac, Branislav; Eberhardt, Martin; Ferrazzi, Fulvia; Kretzschmar, Elke; et al. (Nature, 2019)
Macrophages are considered to contribute to chronic inflammatory diseases such as rheumatoid arthritis1. However, both the exact origin and the role of macrophages in inflammatory joint disease remain unclear. Here we use fate-mapping approaches in conjunction with three-dimensional light-sheet fluorescence microscopy and single-cell RNA sequencing to perform a comprehensive spatiotemporal analysis of the composition, origin and differentiation of subsets of macrophages within healthy and inflamed joints, and study the roles of these macrophages during arthritis. We find that dynamic membrane-like structures, consisting of a distinct population of CX3CR1+ tissue-resident macrophages, form an internal immunological barrier at the synovial lining and physically seclude the joint. These barrier-forming macrophages display features that are otherwise typical of epithelial cells, and maintain their numbers through a pool of locally proliferating CX3CR1− mononuclear cells that are embedded into the synovial tissue. Unlike recruited monocyte-derived macrophages, which actively contribute to joint inflammation, these epithelial-like CX3CR1+ lining macrophages restrict the inflammatory reaction by providing a tight-junction-mediated shield for intra-articular structures. Our data reveal an unexpected functional diversification among synovial macrophages and have important implications for the general role of macrophages in health and disease.
CRIS-Team Scopus Importer:2019-08-16

Metabolic reprogramming of osteoclasts represents a therapeutic target during the treatment of osteoporosis - Taubmann, Jule; Krishnacoumar, Brenda; Böhm, Christina; Faas, Maria; Müller, Dorothea; Adam, Susanne; Stoll, Cornelia; Böttcher, Martin; Mougiakakos, Dimitrios; Sonnewald, Uwe; Hofmann, Jörg; Schett, Georg; et al. (Scientific Reports, 2020)
Osteoclasts are specialised bone resorbing cells that control both physiological and pathological bone turnover. Functional changes in the differentiation and activity of osteoclasts are accompanied by active metabolic reprogramming. However, the biological significance and the in vivo relevance of these events has remained unclear. Here we show that bone resorption of differentiated osteoclasts heavily relies on increased aerobic glycolysis and glycolysis-derived lactate production. While pharmacological inhibition of glycolysis did not affect osteoclast differentiation or viability, it efficiently blocked bone resorption in vitro and in vivo and consequently ameliorated ovariectomy-induced bone loss. Our experiments thus highlight the therapeutic potential of interfering with osteoclast-intrinsic metabolic pathways as possible strategy for the treatment of diseases characterized by accelerated bone loss.
CRIS-Team Scopus Importer:2020-12-11

Metabolic rewiring promotes anti-inflammatory effects of glucocorticoids - Auger, Jean-Philippe; Zimmermann, Max; Faas, Maria; Stifel, Ulrich; Chambers, David; Krishnacoumar, Brenda; Taudte, R. Verena; Grund, Charlotte; Erdmann, Gitta; Scholtysek, Carina; Uderhardt, Stefan; Ben Brahim, Oumaima; et al. (Nature, 2024)
Glucocorticoids represent the mainstay of therapy for a broad spectrum of immune-mediated inflammatory diseases. However, the molecular mechanisms underlying their anti-inflammatory mode of action have remained incompletely understood1. Here we show that the anti-inflammatory properties of glucocorticoids involve reprogramming of the mitochondrial metabolism of macrophages, resulting in increased and sustained production of the anti-inflammatory metabolite itaconate and consequent inhibition of the inflammatory response. The glucocorticoid receptor interacts with parts of the pyruvate dehydrogenase complex whereby glucocorticoids provoke an increase in activity and enable an accelerated and paradoxical flux of the tricarboxylic acid (TCA) cycle in otherwise pro-inflammatory macrophages. This glucocorticoid-mediated rewiring of mitochondrial metabolism potentiates TCA-cycle-dependent production of itaconate throughout the inflammatory response, thereby interfering with the production of pro-inflammatory cytokines. By contrast, artificial blocking of the TCA cycle or genetic deficiency in aconitate decarboxylase 1, the rate-limiting enzyme of itaconate synthesis, interferes with the anti-inflammatory effects of glucocorticoids and, accordingly, abrogates their beneficial effects during a diverse range of preclinical models of immune-mediated inflammatory diseases. Our findings provide important insights into the anti-inflammatory properties of glucocorticoids and have substantial implications for the design of new classes of anti-inflammatory drugs.
CRIS-Team Scopus Importer:2024-04-19

Osteocyte necrosis triggers osteoclast-mediated bone loss through macrophage-inducible C-type lectin - Andreev, Darja; Liu, Mengdan; Weidner, Daniela; Kachler, Katerina; Faas, Maria; Grüneboom, Anika; Schlötzer-Schrehardt, Ursula; Munoz, Luis Enrique; Steffen, Ulrike; Grötsch, Bettina; Killy, Barbara; Krönke, Gerhard; et al. (Journal of Clinical Investigation, 2020)
Although the control of bone-resorbing osteoclasts through osteocyte-derived RANKL is well defined, little is known about the regulation of osteoclasts by osteocyte death. Indeed, several skeletal diseases, such as bone fracture, osteonecrosis, and inflammation are characterized by excessive osteocyte death. Herein we show that osteoclasts sense damageassociated molecular patterns (DAMPs) released by necrotic osteocytes via macrophage-inducible C-type lectin (Mincle), which induced their differentiation and triggered bone loss. Osteoclasts showed robust Mincle expression upon exposure to necrotic osteocytes in vitro and in vivo. RNA sequencing and metabolic analyses demonstrated that Mincle activation triggers osteoclastogenesis via ITAM-based calcium signaling pathways, skewing osteoclast metabolism toward oxidative phosphorylation. Deletion of Mincle in vivo effectively blocked the activation of osteoclasts after induction of osteocyte death, improved fracture repair, and attenuated inflammation-mediated bone loss. Furthermore, in patients with osteonecrosis, Mincle was highly expressed at skeletal sites of osteocyte death and correlated with strong osteoclastic activity. Taken together, these data point to what we believe is a novel DAMP-mediated process that allows osteoclast activation and bone loss in the context of osteocyte death.
CRIS-Team Scopus Importer:2020-10-16

The Nuclear Receptor Nr4a1 Acts as a Microglia Rheostat and Serves as a Therapeutic Target in Autoimmune-Driven Central Nervous System Inflammation - Rothe, Tobias; Ipseiz, Natacha; Faas, Maria; Lang, Stefanie; Perez-Branguli, Francesc; Metzger, Daniel; Ichinose, Hiroshi; Winner, Beate; Schett, Georg; Krönke, Gerhard (Journal of Immunology, 2017)
Microglia cells fulfill key homeostatic functions and essentially contribute to host defense within the CNS. Altered activation of microglia, in turn, has been implicated in neuroinflammatory and neurodegenerative diseases. In this study, we identify the nuclear receptor (NR) Nr4a1 as key rheostat controlling the activation threshold and polarization of microglia. In steady-state microglia, ubiquitous neuronal-derived stress signals such as ATP induced expression of this NR, which contributed to the maintenance of a resting and noninflammatory microglia phenotype. Global and microglia-specific deletion of Nr4a1 triggered the spontaneous and overwhelming activation of microglia and resulted in increased cytokine and NO production as well as in an accelerated and exacerbated form of experimental autoimmune encephalomyelitis. Ligand-induced activation of Nr4a1 accordingly ameliorated the course of this disease. Our current data thus identify Nr4a1 as regulator of microglia activation and potentially new target for the treatment of inflammatory CNS diseases such as multiple sclerosis.
EVALuna2:13374